IMPLEMENTASI METODE WATERFALL PADA PERANCANGAN SISTEM INFORMASI KOPERASI SIMPAN PINJAM BERBASIS WEB DAN ANDROID (STUDI KASUS PT. PEB) - Galuh Saputri; Emi Sita Eriana (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2020)
PEB Cooperative is a savings and loan cooperative which is intended for employees of PT. PEB, is engaged in the garment industry. Established since 15 years with the number of cooperative members who are permanent employees of the company. This cooperative becomes an economical shelter to meet the needs of its employees. Technology in admin data processing is still simple using Microsoft Excel tools, in applications that connect members with admins on this system have not been designed, so from the background of this research will design a web-based and android-based savings and loan cooperative information system This design uses the waterfall model which will take a sequential design making it easier for developers and users. The hope is that this design will help make transactions for savings, loans, deposits, data collection, and reports to members, admins and leaders. The results obtained from the questionnaire with the System Usability Scale method in this savings and loan cooperative application are easy to use, faster, and practical, stated by the cooperative members by 84% and cooperative managers by 80%. It can be concluded that this application that has been designed can make it easier to carry out savings and loan transactions quickly and practically.